Atterberg limits of modified compacted clayey soil for sustainable green subgrade structure - Onyelowe, Kennedy C.; Onyia, Michael E.; Onukwugha, Eze R.; Ezugwu, Charles N.; Odumaded, A.; Obianyo, Ifeyinwa I.; Chigbo, Ikechukwu; Kelechi-Asumba, Sylvia (Penerbit Universiti Kebangsaan Malaysia, 2021)
Atterberg limits are one of the fundamental geotechnical parameters used to assess the settlement and other volume change parameters of engineering soils containing clays. This paper describes index test results on expansive soil treated with rice husk ash (RHA) and 5%, 10%, and 15% quicklime activated rice husk ash (QARHA) obtained using laboratory testing procedure. The cost of conventional binders used in earthwork has necessitated the need to look for cheaper materials that serve the same purpose. Also, the extent of environmental poisoning due to the use of cement is worrisome and has motivated the use of alternative and green supplementary cements in soils stabilization. However, previous research works have dwelt on the use of ash derived from the combustion of solid waste materials like rice husk ash. But the present work has gone a step further to activate the properties of rice husk ash with three proportions of quicklime and this novel procedure has not been reported by any work in recent times. After preliminary tests, the test soil was classified as highly plastic soil. The soil was further subjected to treatment exercise at the rate of 0% (control), 2%, 4%, 6%, 8%, and 10% addition of RHA, 5%-QARHA, 10%-QARHA, and 15%-QARHA by weight of test soil. The RHA addition improved the index properties; liquid and plastic limits and plasticity index at varying rates. The rates of improvement show that the higher the rate of activation of rice husk ash with quicklime, the higher the pozzolanic performance, which tends to cement the soil particles together and improve the consistency through flocculation. Finally, rice husk ash and its composites achieved by quicklime activation process have shown to be alternative cementing construction materials for use as binders in the modification of expansive soils utilized as subgrade materials.